The g-Good-Neighbor Conditional Diagnosability of Locally Exchanged Twisted Cubes. (11th January 2019) - Liu, Hui-qing; Hu, Xiao-lan; Gao, Shan
Abstract: Connectivity and diagnosability are important parameters in measuring the fault tolerance and reliability of interconnection networks. The R g -vertex-connectivity of a connected graph G is the minimum cardinality of a faulty set X ⊆ V ( G ) such that G − X is disconnected and every fault-free vertex has at least g fault-free neighbors. The g -good-neighbor conditional diagnosability is defined as the maximum cardinality of a g -good-neighbor conditional faulty set that the system can guarantee to identify. The interconnection network considered here is the locally exchanged twisted cube L e T Q ( s, t ) . For 1 ≤ s ≤ t and 0 ≤ g ≤ s, we first determine the R g -vertex-connectivity of L e T Q ( s, t ), then establish the g -good-neighbor conditional diagnosability of L e T Q ( s, t ) under the PMC model and MM* model, respectively.